Banks’ risk taking and creditors’ bargaining power - Heller, Yuval; Peleg Lazar, Sharon; Raviv, Alon (Journal of Corporate Finance, 2022)
We study the influence of unsecured debt (subordinated debt) on banks’ risk-taking in a contingent claim model where assets are risky debt claims. We consider the bargaining between stockholders and debtholders when choosing the level of asset risk. Replacing part of a bank's stock with subordinated debt leads to risk-shifting events occurring in a narrower domain of asset values (leverage ratios), but can lead to higher levels of risk, depending on the relative bargaining power. When side payments between the bank's claimholders are possible the inclusion of subordinated debt does not affect asset risk. Moreover, we show that severe, yet infrequent, regulatory corrective measures might have adverse effects on risk-shifting.